Dominica. Significant achievements 2016 - Instituto Interamericano de Cooperación para la Agricultura (IICA) (Instituto Interamericano de Cooperación para la Agricultura (IICA), 2017)
The main activities carried out by the Institute in Dominica during 2016 are identified, with respect to the needs and interests of the country, strengthening issues such as governance, public policy, leadership, technology, sustainability, methodologies, good agricultural practices, resilience against change climate and management of forest and soil resources. Finally, we worked on packaging, export and standards labeling.